Evaluating short-term changes in L2 complexity development - Bulté, Bram; Housen, Alex (Círculo de Lingüística Aplicada a la Comunicación, 2015)
This paper reports on a study on the nature and extent of the development of English L2 writing proficiency of 45 adult ESL learners over the time of an intensive short-term EAP program as evaluated by means of objective measures targeting different components of lexical and syntactic complexity. In addition, we compare the scores on these measures with more holistic and subjective ratings of learners' overall writing quality. Results reveal that some measures, but not necessarily the most popular linguistic complexity measures (e.g., subordination ratios and lexical richness measures), can indeed adequately and validly capture development in L2 writing in short-term ESL courses. Results further suggest that different subcomponents of syntactic and lexical complexity in L2 writing develop at different rates, which stressed the importance of calculating a sufficiently wide range of complexity measures in order to obtain a comprehensive picture of L2 development.